Prophetic medicine as potential functional food elements in the intervention of cancer: a review - Sheikh, Bassem Yousef A.; Sarker, Md Moklesur Rahman; Kamarudin, Muhamad Noor Alfarizal; Ismail, Amin (Elsevier Masson, 2017)
Amounting scientific evidences have revealed the antitumor, antimetastatic, antiangiogenic, antiproliferative, chemopreventive and neo-adjuvant efficacy of Prophetic Medicine in various in vitro, in vivo and clinical cancer models. Prophetic Medicine includes plants, dietary materials or spices that were used as remedy recipes and nutrition by the great Prophet Mohammed (peace be upon him) to treat various ailments. Prophetic medicine is the total authentic Hadith narrated by the Prophet (PBUH) in relation to medicine, whether Qur’anic verses or honourable Prophetic Hadith. The ability of functional foods from Prophetic Medicine to modulate various signalling pathways and multidrug resistance conferring proteins with low side-effects exemplify their great potential as neo-adjuvants and/or chemotherapeutics. The present review aims to provide the collective in vitro, in vivo, clinical and epidemiology information of Prophetic Medicines, and their bioactive constituents and molecular mechanisms as potential functional foods for the management of cancer.